2018
DOI: 10.1007/5584_2017_121
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Pectus Excavatum by the Nuss Procedure: A 15-Year Experience Study

Abstract: Pectus excavatum is the most common congenital deformity of the chest. The Nuss procedure is minimally invasive surgical correction of this defect, using retrosternal metal bars. The purpose of the present study was to describe a 15-year experience with the Nuss surgery, and to evaluate the long-term clinical results of the procedure. We retrospectively evaluated 239 patients, aged 14-34, who underwent the Nuss surgery in the years 2002-2016. Postoperative complications were observed in 40/236 (16.9%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…10 12 Cierpikowski et al described an overall increase in complications with the placement of multiple bars, although specific complications were not detailed. 13 With univariate analysis, our study identified a significant increase in odds of pleural effusion, postoperative thoracostomy tube placement, and readmission. After further controlling for possible confounding variables, multivariate analysis confirmed an increase in odds of readmission.…”
Section: Discussionmentioning
confidence: 76%
“…10 12 Cierpikowski et al described an overall increase in complications with the placement of multiple bars, although specific complications were not detailed. 13 With univariate analysis, our study identified a significant increase in odds of pleural effusion, postoperative thoracostomy tube placement, and readmission. After further controlling for possible confounding variables, multivariate analysis confirmed an increase in odds of readmission.…”
Section: Discussionmentioning
confidence: 76%
“…Починаючи з перших публікацій методики у 1998 р. D. Nuss, у всьому світі відбулася революція в лікуванні цієї патології. Провідні хірурги, які займаються ЛДГК, почали працювати в напрямку вдосконалення методики, пріоритетом, звичайно ж, залишалася безпечність операції [4,8,9]. Так, процедура корекції запалої грудної клітки за методикою Nuss передбачає торакоскопічний контроль, що дає змогу безпечніше виконувати маніпуляції всередині грудної клітки та забезпечувати адекватний гемостаз, за потреби [12].…”
Section: оригінальні дослідження торакальна хірургіяunclassified
“…However, in the case of adults, the original Nuss procedure requires some modifications [Jaroszewski et al, 2018]. A 15 year-experience in Nuss surgical correction of 239 patients aged between 14-34 are summarized in the study [Cierpikowski et al, 2018]. The authors observed beneficial long-term effects in 96.7% of the pectus patients, and postoperative complications in 16.9% of them, mostly in the adult patients with asymmetric chest deformations.…”
Section: Chest Wall Deformations and Their Treatmentmentioning
confidence: 99%